Erythrodermic psoriasis: a case report and literature review - Ferreira, Ana Carolina A de F; Anjos, Fernanda SA dos; Yoshino, Patrícia M; Hal, Lívia S; Pinto, Simone CC; Lima, Ricardo B (Medicina (Ribeirao Preto), 2014)
Erythroderma is a rare syndrome, responsible for diffuse erythema and scaling, affecting more than 80 or 90% of the body surface. It is potentially serious, because of the association with electrolyte disturbances and bacterial colonization. Among the etiological causes are present: primary dermatological diseases,allergic reaction to certain drugs, systemic diseases, and neoplasms. In this case report, we illustrate an example of severe and acute erythroderma initially treated with systemic steroids. The skin biopsy indicated the diagnosis of erythrodermic psoriasis, which responded well to treatment with cyclosporine, acitretin and etanercept. Based on this report, we reviewed the literature on the causes of exfoliative dermatitis and discussed the management of severe cases of psoriasis.